2022
DOI: 10.3322/caac.21767
|View full text |Cite
|
Sign up to set email alerts
|

Cancer care for people with dementia: Literature overview and recommendations for practice and research

Abstract: As many countries experience population aging, patients with cancer are becoming older and have more preexisting comorbidities, which include prevalent, age-related, chronic conditions such as dementia. People living with dementia (PLWD) are vulnerable to health disparities, and dementia has high potential to complicate and adversely affect care and outcomes across the cancer trajectory. This report offers an overview of dementia and its prevalence among patients with cancer and a summary of the research liter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 159 publications
(500 reference statements)
0
7
0
Order By: Relevance
“…Ashley et al. [6] found dementia patients have difficulty noticing new symptoms, especially acknowledging them as potential cancer signs and appreciating cancer's seriousness, and thus may not report symptoms to caregivers or clinicians and may cause diagnostic overshadowing.…”
Section: Discussionmentioning
confidence: 99%
“…Ashley et al. [6] found dementia patients have difficulty noticing new symptoms, especially acknowledging them as potential cancer signs and appreciating cancer's seriousness, and thus may not report symptoms to caregivers or clinicians and may cause diagnostic overshadowing.…”
Section: Discussionmentioning
confidence: 99%
“…She refused to be referred by the GP several times because of her severe dementia. Research has shown that people living with dementia (PLWD) are vulnerable to health disparities, so dementia has the high potential to complicate and adversely affect care outcomes across the cancer trajectory 1 …”
Section: Figurementioning
confidence: 99%
“…Research has shown that people living with dementia (PLWD) are vulnerable to health disparities, so dementia has the high potential to complicate and adversely affect care outcomes across the cancer trajectory. 1 This patient's husband brought her to our service because the mass was causing daily difficulties (bleeding and pain during wound care). The mass was excised and reconstructed in one surgery.…”
mentioning
confidence: 99%
“…For example, comprehensive assessment must not only involve gauging the extent to which a patient is able to participate in their own treatment decision making, but also involving often one or more family members or caregivers. These persons may or may not have a legally appointed role for decision making and may have opinions which differ or conflict with the patient [37].…”
Section: Cognitive Assessmentmentioning
confidence: 99%